Social Media as Self Existence in Students Using Tiktok Applications - Diki Affandi; Isna Wijayani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Tik Tok is an application that provides unique and interesting special effects that users of this application can easily use to create cool short videos that can attract the attention of many people who see it. The Tik Tok application is a Chinese social network and music video platform that was launched in September 2016. This application is a short video creation application with music support that is very popular with many people, including adults and minors. This Tik Tok application can also make its users known or famous. The existence of adolescents is important in socializing. The existence of teenagers is also a symbol that teenagers can get along and choose connections with other people. Existing for a teenager is a pleasure in itself. Because its existence is often connoted with pleasant things. For example, having lots of friends and connections, being an important person and some of the pleasures of being with other teenagers like being able to express themselves freely and doing things that are trending for other teenagers. This is what makes the lifestyle of teenagers in general change. They try to always exist so that sometimes they are too exaggerated and wrong in their search for existence. This research uses a qualitative research type with a phenomenological approach, and the location of the research is at Syulthan Thaha Saifuddin State Islamic University Jambi, and the data collection method uses observation, interviews, and documentation, data sources are taken from local officials, and interviews with users of the Tiktok application. The data that has been collected is then analyzed using a qualitative descriptive method. Kata Kunci: Media sosial Tik Tok, Eksistensi Diri, Kretifitas